Policy implementation in housing: a study of the experience of Portsmouth and Derby, 1945-74 - Cook, J.A. (1985)
The germ of this thesis was born when the author read "Implementation" by J.A. Pressman and A. Wildavsky. This book stimulated the author's interest in the interpretation of Central Government policy by local authorities of differing political complexions. This thesis reviews and researches the impact of the implementation of Central Government policy by local authorities and attempts to assess the reasons for divergence in policy between Conservative and Labour controlled authorities. The question posed is whether politics accounts largely or wholly for policy divergences, or whether it is other factors. From the research undertaken by the author, it would appear that political complexion is only one factor in a very complex network of influences upon policy implementation. The thesis covers factors such as the personality of the actors involved, inter and intra departmental relationships, and professional linkages as well as the more traditional elements of local and central government interactions. The focus is on the implementation of housing policy in Portsmouth, a predominantly Conservative controlled authority, and Derby, a predominantly Labour controlled authority, during the period 1945 to 1974.Both authorities were faced by similar problems in the period reviewed, and yet each adopted its own distinct policy, as the skylines of the two cities reflect today.